2018
DOI: 10.21873/anticanres.12788
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Adrenal Metastases with Conventional or Hypofractionated Image-guided Radiation Therapy – Patterns and Outcomes

Abstract: Stereotactic radiotherapy of adrenal metastases was safe and effective in patients with oligometastases or oligoprogression. In palliative patients, short-course radiotherapy complemented with supportive care should be preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 16 publications
1
31
1
Order By: Relevance
“…In our study, no late gastrointestinal or renal toxicities were found, which was consistent with the previous studies [ 25 28 ]. Only two patients developed multiple gastric or duodenal ulcer [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, no late gastrointestinal or renal toxicities were found, which was consistent with the previous studies [ 25 28 ]. Only two patients developed multiple gastric or duodenal ulcer [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar outcomes were also found in Franzese et al with the median OS of 28.5 months and 1-year and 2-year LC rates of 65.5% and 40.7%, respectively [ 27 ]. Nevertheless, the median OS was inferior than those in the above studies when patients received SBRT or conventional radiotherapy [ 28 ], which might be attributable to lower BED 10 compared with those of SBRT. The findings in current study were consistent with previous studies.…”
Section: Discussionmentioning
confidence: 96%
“…Limitations to this study were mainly caused by the retrospective nature of this analysis. Patient numbers were rather low, but similar to other studies, as adrenal SBRT is still not offered to many patients [3,21,22,24,36,43,45]. Furthermore, for increasing strength and homogeneity of our study, we only focused our analysis on truly oligometastatic or oligoprogressive patients and excluded all patients who were treated with palliative intent or dose.…”
Section: Discussionmentioning
confidence: 96%
“…While SBRT is well established and widely applied in the treatment of pulmonary and hepatic oligometastases [17][18][19][20], the literature for adrenal metastases is scarce. Predominantly small and retrospective studies exist which do not primarily focus on oligometastatic or oligoprogressive disease, but also include patients treated with palliative intent [21][22][23][24][25][26][27]. Furthermore, these studies only report limited details on radiotherapy planning and requirement for forced dose restrictions due to the close proximity to radiosensitive organs-at risks (OARs).…”
Section: Introductionmentioning
confidence: 99%
“…After 16 months a local control of 86.7% was seen and no toxicity greater or equal to grade 3 [18]. Buergy et al also report an average local disease-free survival of 18.3 months [19].…”
Section: Discussionmentioning
confidence: 87%